Representing Islamic Values: Contemporary Indonesian ‎Children’s Literature as a Resource for Religious Literacy - Yenni Hayati; Ridha Hasnul Ulya; Abdurahman; Nofrahadi; Rafdisyam (JPI: Jurnal Pustaka Indonesia, 2026)
This study aims to examine the potential of contemporary Indonesian children's literature as a catalytic medium in the teaching of religious values, religious literacy, and character formation among students in Islamic elementary schools (madrasah ibtidaiyah). Employing a qualitative approach and content analysis, the research explores the representation of values related to aqidah (faith), akhlaq (ethics), and ibadah (worship) within ten selected novels from the Kecil-Kecil Punya Karya (KKPK) series published by Mizan. The findings reveal that children’s literature is capable of conveying Islamic teachings in a contextualized manner, using narratives that resonate with the world of young readers. Values such as birrul walidain (respecting parents), prayer, Qur’an recitation, and wearing the hijab are portrayed through the behavior of main characters, dialogues, and storylines that are simple yet profoundly meaningful. Furthermore, children’s literature contributes to enhancing empathy, moral awareness, and the religious identity of young readers. The study also finds that integrating children’s literature into the madrasah curriculum can serve as an effective strategy for strengthening character education rooted in Islamic values. Through a non-dogmatic approach, children's literature facilitates the natural and enjoyable internalization of religious values. As an implication, teachers and policymakers are encouraged to utilize children’s literature as an integral component of thematic learning in Islamic schools.